This preview shows page 1. Sign up to view the full content.
39
(a) (Review)
Gz
=
·
cz
1
+
sz
2
sz
1
−
cz
2
¸
=
x
e
1
Multiplying the frst equation by
c
, the second by
s
, and adding yields
(
c
2
+
s
2
)
z
1
=
cx ,
so
c
=
z
1
/x .
Similarly, we can determine that
s
=
z
2
/x .
Since
c
2
+
s
2
= 1, we conclude that
z
2
1
+
z
2
2
=
x
2
,
so we can take
c
=
z
1
p
z
2
1
+
z
2
2
,
s
=
z
2
p
z
2
1
+
z
2
2
.
(b) The frst rotation matrix is chosen to zero
a
61
. The second zeros the resulting
entry in row 6, column 2, and the fnal one zeros row 6, column 3.
CHALLENGE 7.6.
See
This is the end of the preview. Sign up
to
access the rest of the document.
This note was uploaded on 01/21/2012 for the course MAP 3302 taught by Professor Dr.robin during the Fall '11 term at University of Florida.
 Fall '11
 Dr.Robin

Click to edit the document details